Enhancing Patient Safety through Legal Reform: A Comparative Review of Healthcare Best Practices and Legal Frameworks - Hutagaol, Roy Richardo; Fikri , Ahmad Ma’mun (LifeSciFi, 2025)
Patient safety has become a global health priority, closely linked to the quality of medical services and the legal framework governing healthcare systems. This study aims to juridically and comparatively examine the regulatory frameworks of patient safety across various jurisdictions and analyze the contrasting approaches between developed and developing countries. Using a qualitative method with a literature review approach, data were collected from scientific journals, international health organizations such as the World Health Organization, government regulations, and previous empirical studies. The findings indicate that developed nations have implemented more structured patient safety regulations, characterized by mandatory, privileged incident reporting systems and legal protection for healthcare professionals (whistleblowers). In stark contrast, developing countries, including Indonesia, face persistent challenges related to limited resources, weak legal enforcement, and a prevalent blame culture that hinders open reporting. The comparative analysis highlights the critical need for legal reform in Indonesia to strengthen patient safety regulations, particularly through the revision of the hospital law, the integration of telemedicine into the legal framework, and the establishment of a transparent, protected reporting system. Ultimately, strengthening legal frameworks is essential to ensure that patient safety becomes a fundamental, enforceable, and systemic element of health systems worldwide.